Evaluation of satisfaction with geospatial assistive technology (ESGAT): a methodological and usability study. - Vincent, Claude; Girard, Rébecca; Dumont, Frédéric; Archambault, Philippe; Routhier, François; Mostafavi, Mir Abolfazl (Disability & Rehabilitation: Assistive Technology, 2022)
Manual wheelchair users are more vulnerable, in situations such as road crossings, hazardous sidewalks or curbs and crossing of buildings and facilities threshold. Geospatial assistive technology (GAT) can help with route planning. However, it is important to ensure the usability of such products, as well as the satisfaction of persons with reduced mobility. The study's aim was (1) to develop and validate a questionnaire on the satisfaction of GAT, in English and French, and to (2) assess satisfaction, efficacy and efficiency of a GAT with manual wheelchair users following a filmed trial in a dense urban area. A methodological study was conducted (development of the questionnaire, assessment of its content validity, feasibility and practicability) followed by a trial and post-observations with the videos. Two questionnaires (English, French) were concurrently validated by two groups of experts (n = 8), and then field-tested by wheelchair users (n = 8), using Google Maps Pedestrian routeing tool. The Evaluation of satisfaction with geospatial assistive technology (ESGAT) consists in a user profile and their experience with the technology, followed by 12 satisfaction criteria rated from 1-not satisfied to 5-very satisfied. Both questionnaires were rated as feasible and practicable to complete. The usability of Google Maps Pedestrian routeing tool was measured as "moderate" by manual wheelchairs since the total satisfaction score at the ESGAT was 3.9/5 (quite satisfied). The items with the lowest score were navigation assistance, hands-free function and security. The GAT was effective (87.5% have completed their destination) but not efficient (37.5% needed help). For manual wheelchair users paired with geospatial assistive technology: • A 10 minutes questionnaire was developed and validated to assess their satisfaction after testing aid in an urban area. • Satisfaction criteria to address are ease of access (service), learnability, hands-free function, ease of use for planning as well for navigating, transportability/ appearance, content, geographic information, effectiveness, efficiency, navigation assistance and security • A field test is necessary to ensure the effectiveness of the technology in avoiding or announcing potential obstacles such as sidewalk crossing ramp, damaged and congested sidewalk; sidewalk tilt (side slopes); thresholds at destination; verbal indication too soon or too late; incorrect indication; the arrow does not indicate the right direction; readjustment of the route needed; a lack of indication; and human intervention needed.